Genetics and Glaucoma: the state of the art - Tirendi, Sara; Domenicotti, Cinzia; Bassi, Anna Maria; Vernazza, Stefania (Frontiers in Medicine, 2023)
Glaucoma is the second leading cause of irreversible blindness worldwide. Although genetic background contributes differently to rare early-onset glaucoma (before age 40) or common adult-onset glaucoma, it is now considered an important factor in all major forms of the disease. Genetic and genomic studies, including GWAS, are contributing to identifying novel loci associated with glaucoma or to endophenotypes across ancestries to enrich the knowledge about glaucoma genetic susceptibility. Moreover, new high-throughput functional genomics contributes to defining the relevance of genetic results in the biological pathways and processes involved in glaucoma pathogenesis. Such studies are expected to advance significantly our understanding of glaucoma's genetic basis and provide new druggable targets to treat glaucoma. This review gives an overview of the role of genetics in the pathogenesis or risk of glaucoma